Microstructural and Wear Characteristics of High Velocity Oxygen Fuel (HVOF) Sprayed NiCrBSi-SiC Composite Coating on SAE 1030 Steel - Buytoz, Soner; Ulutan, Mustafa; Islak, Serkan; Kurt, Bulent; Celik, O. Nuri (Springer Heidelberg, 2013)
In this paper, wear properties of NiCrBSi-SiC coatings were investigated using the ball-on-disk wear test. In experimental study, NiCrBSi-SiC powders were sprayed using a high-velocity oxygen fuel technique on an SAE 1030 steel substrate. Powder mixtures with different weight mixing ratios, NiCrBSi + 10 wt% SiC, NiCrBSi + 20 wt% SiC and NiCrBSi + 40 wt% SiC coatings were prepared. The deposited coatings are compared in terms of their phase composition, microstructure and hardness. It is proved that the degree of mixing of the NiCrBSi and SiC components in the powder has a massive effect on the phase composition, microstructure and hardness of the coatings. Wear tests were conducted on both the uncoated and coated substrates at same normal load, speed, and wear distance. It has been determined that the coated substrates exhibit a very good tribological performance in comparison to the uncoated substrate. The increase in the adhesive wear resistance provided by the coating has been attributed to the presence of a large amount of dispersed Ni and Cr carbide and/or borides in the Ni matrix.
Keywords: NiCrBSi-based coating; SiC powder; HVOF; Wear performance